2013
DOI: 10.1016/j.jpsychires.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic neuroactive steroids and resting-state functional connectivity in postpartum depression: A preliminary study

Abstract: Postpartum depression (PPD) affects up to 1 in 8 women. The early postpartum period is characterized by a downward physiological shift from relatively elevated levels of sex steroids during pregnancy to diminished levels after parturition. Sex steroids influence functional brain connectivity in healthy non-puerperal subjects. This study tests the hypothesis that PPD is associated with attenuation of resting-state functional connectivity (rs-fc) within corticolimbic regions implicated in depression and alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 75 publications
(86 reference statements)
5
120
1
1
Order By: Relevance
“…Furthermore, there is a growing literature on the important role of reproductive hormones in modulating neural circuits and biological systems implicated in depression, suggesting that the characteristic hormone instability of the perinatal period could contribute to mood dysregulation in post-partum depression. 14,29 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a growing literature on the important role of reproductive hormones in modulating neural circuits and biological systems implicated in depression, suggesting that the characteristic hormone instability of the perinatal period could contribute to mood dysregulation in post-partum depression. 14,29 …”
Section: Discussionmentioning
confidence: 99%
“…Significant research links low levels of allopregnanolone to depressed mood Eser et al, 2006;Le Melledo and Baker, 2004;Padberg et al, 2002;Pinna et al, 2006;Schule et al, 2014;Strohle et al, 1999;Uzunova et al, 2006) and other evidence links mood states or histories thereof with alterations in the ratio of allopregnanolone to its precursors (Girdler et al, 2012;Schiller et al, 2014). In the perinatal period specifically, Deligiannidis et al (2013), in a small sample, found no relationship between pregnancy allopregnanolone and the development of PPD, whereas Hellgren et al (2014) found significantly lower levels of allopregnanolone in depressed pregnant women when compared with healthy controls (Hellgren et al, 2014). In a separate analysis, our group found that low levels of allopregnanolone measured in the second trimester predicted the development of PPD (p = 0.01); this effect was driven by women who were euthymic in the second trimester (Osborne et al, under review).…”
Section: Discussionmentioning
confidence: 99%
“…A second study by Deligiannidis et al . (146) of eight PPD and nine healthy mothers studied at 9 weeks postpartum similarly showed attenuated functional connectivity in numerous corticolimbic circuits, including coupling within the DMN of ACC, inferior parietal cortex and precuneus, as well as between DMN nodes and amygdala. A contradictory report by Xiao-juan et al .…”
Section: Default Mode Networkmentioning
confidence: 97%